Fabrication of Large Area, Ordered Nanoporous Structures on Various Substrates for Potential Electro-Optic Applications - Hongsub Jee; Kiseok Jeon; Min-Joon Park; Jaehyeong Lee (Applied Sciences, 2021)
Nanoporous structures have attracted great attention in electronics, sensor and storage devices, and photonics because of their large surface area, large volume to surface ratio, and potential for high-sensitivity sensor applications. Normally, electron or ion beam patterning can be used for nanopores fabrication by direct writing. However, direct writing is a rather expensive and time-consuming method due to its serial nature. Therefore, it may not translate to a preferred manufacturing process. In this research, a perfectly ordered large-area periodic pattern in an area of approximately 1 cm2 has been successfully fabricated on various substrates including glass, silicon, and polydimethylsiloxane, using a two-step process comprising visible light-based multibeam interference lithography and subsequent pattern transfer processes of reactive ion etching and nanomolding. Additionally, the multibeam interference lithography templated anodized aluminum oxide process has been described. Since the fabrication area in multibeam interference lithography can be extended by using a larger beam size, it is highly cost effective and manufacturable. Furthermore, although not described here, an electrodeposition process can be utilized as a pattern transfer process. This large-area perfectly ordered nanopore array will be very useful for high-density electronic memory and photonic bandgap and metamaterial applications.